Unlocking the potential of multilevel inverters: a comprehensive review - Khadar, Shaik Abdul; Shuaib, Y. Mohamed; Kubendran, Vadivel; Bharanigha, Veerasamy (Institute of Advanced Engineering and Science, 2025)
The energy usage of the electricity system increased dramatically during the last few years as a result of the rise in consumers and businesses. It resulted in large-scale traditional energy generation, causing an increase in global emissions. As a result, the perforation of sources that are renewable inside electrical networks has greatly grown. Solar power systems (PS) have grown into the most prominent sources because of their tremendous potential; hence, global installed solar power capability has expanded beyond more than 635 gigawatts (GW), representing about 2% of the world’s energy consumption. Multilevel inverters (MLI) are now on top of two-level inverters due to their ability to deliver diminished electromagnetic interference (EMI) and elevated capability. This study examines MLIs in terms of categorization, development, and problems, as well as practical advice for use in renewable energy systems (RES). This review also emphasizes the significance and development of an improved multilevel inverter. In summary, this study focuses on the usage of multilayer inverters in PV systems to stimulate and assist society in developing efficient, cost-effective inverters with integrated capacities of those converters described in the survey.